2009
DOI: 10.1007/s11434-009-0472-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of typhoon Matsa on ionospheric TEC

Abstract: The effects of typhoon Matsa on the ionosphere are studied by using GPS-TEC data observed at about 50 GPS stations. It is shown that the ionosphere has been already influenced and TEC tends to increase before the landing of Matsa, and the difference of TEC from its monthly median over the typhoon area is about 5 TECU. With the landing of Matsa, both the magnitude and the area of increased TEC decrease. One day after the landing of Matsa, TEC reaches its minimum and is lower than the monthly median. In comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 17 publications
2
30
0
4
Order By: Relevance
“…2b), because the instantaneous variations in B0bot are dependent on height of particular Ne concentration which varies rapidly for day-to-day and hour-to-hour (Lee and Reinisch, 2006;Sethi and Mahajan, 2002), whereas BIEC is the sum up of vertical Ne concentration bellow HmF2 representing the bottom side Ne shape profile (Sethi and Dabas, 2006). Some studies (Tian et al, 2010;Lin, 2012aLin, , 2012b have addressed that the ionospheric TEC increased by noticeable amount before landing of Typhoons and its highest variation amplitude was detected at the most intense state of the cyclone when wind speed and area (of typhoon), both are maximum. But, the analysis we carried out has revealed that the B0bot and BIEC values noticeably increased in comparison to T0top and TIEC near the intense state of the CGPs which indirectly helps to diminish both Rtb and ECR to a decisive level.…”
Section: Diurnal Variations Of Ecr and Rtbmentioning
confidence: 99%
See 1 more Smart Citation
“…2b), because the instantaneous variations in B0bot are dependent on height of particular Ne concentration which varies rapidly for day-to-day and hour-to-hour (Lee and Reinisch, 2006;Sethi and Mahajan, 2002), whereas BIEC is the sum up of vertical Ne concentration bellow HmF2 representing the bottom side Ne shape profile (Sethi and Dabas, 2006). Some studies (Tian et al, 2010;Lin, 2012aLin, , 2012b have addressed that the ionospheric TEC increased by noticeable amount before landing of Typhoons and its highest variation amplitude was detected at the most intense state of the cyclone when wind speed and area (of typhoon), both are maximum. But, the analysis we carried out has revealed that the B0bot and BIEC values noticeably increased in comparison to T0top and TIEC near the intense state of the CGPs which indirectly helps to diminish both Rtb and ECR to a decisive level.…”
Section: Diurnal Variations Of Ecr and Rtbmentioning
confidence: 99%
“…Due to the coincidence of Tropical Cyclone (TC) with geomagnetic storm the authors in Afraimovich et al (2008) could not manage to detect the disturbance due to the generation of typhoon SAOMAI. Lin (2012aLin ( , 2012b, Polyakova and Perevalova (2013) and Tian et al (2010) also have analyzed the TEC variations in the low-latitude ionosphere during typhoons. Their analysis showed that the TEC in ionosphere near the TC genesis area has a large increase which had an important impact on the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The description of quasi-sinusoidal oscillations recorded during severe thunderstorms was given in Jones, 1971, Davies andJones, 1973;Prasad et al, 1975). Some authors (Shen, 1982;Okuzawa et al, 1986;Bishop et al, 2006;Perevalova and Polekh, 2009;Mao et al, 2010;Polyakova and Perevalova, 2011;Lin, 2012;Chernigovskaya et al, 2014a) revealed middle-and large-scale TIDs at the F2 layer heights during the development stage of tropical cyclones. There were also recorded other ionospheric effects of meteorological disturbances: infrasonic oscillations, electric fields, heating, optical emissions, scattering in the F layer (F-spread) (Inan et al, 1991;Taranenko et al, 1993;Huang and Kelly, 1996;Martinis and Manzano, 1999;Isaev et al, 2002;Šindelářová et al, 2009bŠindelářová et al, , Perminov et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Tao et al (2010) concluded that typhoons caused a short increase in foF2 before the landing and a persistent decrease after landing. The effects of typhoon Matsa on the ionosphere were studied by Mao et al (2010) using TEC (Total Electron Content) data observed at about 50 GPS stations. They found that the evolution of TEC variations had the same tendency as the typhoon-induced foF2.…”
Section: Introductionmentioning
confidence: 99%